Sailing true north : ten admirals and the voyage of character - Stavridis, James (Penguin Press, 2019)
Admiral Stavridis brings a lifetime of reflection to bear on the subjects of his study--on naval history, on the vocation of the admiral with its special tests and challenges, and on the sweep of global geopolitics. Above all, this is a book that will help you navigate your own life's voyage: the voyage of leadership of course, but more important, the voyage of character. Sadly, evil men can be effective leaders sailing toward bad ends; ultimately, leadership without character is like a ship underway without a rudder. Sailing True North helps us find the right course to chart. Simply as epic lives, the tales of these ten admirals offer up a collection of the greatest imaginable sea stories. Moreover, spanning 2,500 years from ancient Greece to the twenty-first century, Sailing True North is a book that offers a history of the world through the prism of our greatest naval leaders. None of the admirals in this volume were perfect, and some were deeply flawed. But from Themistocles, Drake, and Nelson to Nimitz, Rickover, and Hopper, important themes emerge, not least that there is an art to knowing when to listen to your shipmates and when to turn a blind eye; that serving your reputation is a poor substitute for serving your character; and that taking time to read and reflect is not a luxury, it's a necessity.